Центральний державний електронний архів України: пошук відповідей на виклики часу - Лавренюк, А. (Архіви України, 2008)
Information is focused on tasks and functions of the recently established Central State Electronic Archives of Ukraine, its organization structure as well as the first organizational measures. Special emphasis is made on vital necessity in terms of the development of the legislative and methodical base on certain important issues to be accomplished by CSEAU (or with its assistance).